2011
DOI: 10.1177/0892705711411341
|View full text |Cite
|
Sign up to set email alerts
|

Thickness effect on flame spread characteristics of expanded polystyrene in different environments

Abstract: The objective of this study was to reveal flame spread characteristics of the insulation material, expanded polystyrene (EPS) with different thicknesses under different environmental conditions (pressure and oxygen concentration). Experiments were carried out in small-scale flame spread experimental benches in the Tibetan plateau and Hefei, respectively, with EPS sample sheets inclined horizontally. Changes in the flame spread speed, average length of the pool fire, average maximum flame height, and maximum fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Both the convective heat flux and radiative heat flux of the surface flame decrease due to Sidewall Effect I. Sidewall Effect III could also weaken the surface flame. Huang et al [19] demonstrated that surface flame influences flame spread rate significantly, while pool flame (similar to the adherence flame in this work) contributes little to spread rate. Therefore, flame spread deceleration was observed in this work.…”
Section: Effects Of Sidewallsmentioning
confidence: 96%
See 1 more Smart Citation
“…Both the convective heat flux and radiative heat flux of the surface flame decrease due to Sidewall Effect I. Sidewall Effect III could also weaken the surface flame. Huang et al [19] demonstrated that surface flame influences flame spread rate significantly, while pool flame (similar to the adherence flame in this work) contributes little to spread rate. Therefore, flame spread deceleration was observed in this work.…”
Section: Effects Of Sidewallsmentioning
confidence: 96%
“…Most of the pyrolysis gas from the cross section is pushed by the front air flow to the gypsum board. Thus the surface flame, which is an important factor influencing flame spread [19], is weakened. Furthermore, the surface flame angle θ becomes larger under the effect of front air flow (Fig.…”
Section: Effects Of Sidewallsmentioning
confidence: 99%
“…It was found that the heat transfer mechanism had changed with different sample widths: the flame spread was controlled by convection transfer regime initially while gradually changed to radiation regime as the sample width increased. Huang et al (2011Huang et al ( , 2012 and Jiang et al (2013Jiang et al ( , 2014 investigated the different combustion behaviors of XPS and expanded polystyrene (EPS). Qualitative observations of some thermal properties with some theoretical analysis were provided.…”
Section: Introductionmentioning
confidence: 99%
“…Various research on ETICSs is focused on the probability of fire spread, fire safety, and fire barrier influence on ETICS reaction to fire performance. However, little knowledge is available on influence surface preparation mortar, reinforcing mesh, EPS thickness, and other treatment on the ETICS reactionto-fire performance [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%